Fiscal-Monetary-Financial Stability Interactions in a Data-Rich Environment - Martin Hodula; Lukáš Pfeifer (Review of Economic Perspectives, 2018)
In this paper, we shed some light on the mutual interplay of economic policy and the financial stability objective. We contribute to the intense discussion regarding the influence of fiscal and monetary policy measures on the real economy and the financial sector. We apply a factor-augmented vector autoregression model to Czech macroeconomic data and model the policy interactions in a data-rich environment. Our findings can be summarized in three main points: First, loose economic policies (especially monetary policy) may translate into a more stable financial sector, albeit only in the short term. In the medium term, an expansion-focused mix of monetary and fiscal policy may contribute to systemic risk accumulation, by substantially increasing credit dynamics and house prices. Second, we find that fiscal and monetary policy impact the financial sector in differential magnitudes and time horizons. And third, we confirm that systemic risk materialization might cause significant output losses and deterioration of public finances, trigger deflationary pressures, and increase the debt service ratio. Overall, our findings provide some empirical support for countercyclical fiscal and monetary policies.
Keywords: 330; financial stability; fiscal policy; macroprudential policy; monetary policy; interactions; policy mix